Diagnosis and management of necrotizing fasciitis in the light of the recent recommendations - C. O. Kosulnikov; V. N. Lisnichaya; A. M. Besedin; S. І. Karpenko; S. A. Tarnopolsky; K. V. Kravchenko; A. S. Kudriavtsev (Сучасні медичні технології)
Summary: Necrotizing fasciitis is a rare but life-threatening infection of the soft tissues. It is characterized by spreading inflammation and necrosis starting from the fascia, muscles, and subcutaneous fat, with subsequent necrosis of the overlying skin. Necrotizing fasciitis is classified into four types, depending on microbiological findings. The diagnosis of this disease is difficult. Late diagnosis is observed in 85–100% of cases and is considered the only cause of deaths. Emergency surgical debridement is the primary management modality for necrotizing fasciitis. Vacuum assisted closure therapy is fast and effective wound closure method. Antibiotics and surgical debridement play a key role in the treatment of necrotizing fasciitis.In our hospital, there were 75 patients with necrotizing fasciitis in the last 5 years (type I – 92%, type II – 8%). We observed localization of necrotizing fasciitis in the perineum (32%), upper extremities and chest (25%), lower extremities (28%), abdominal wall and retroperitoneal space (15%). Mortality was 9,5%.